PENYULUHAN DAN PELATIHAN AGRO-ENTREPRENEURSHIP BAGI KELOMPOK UKM SARI MAJU DI DESA MENGWI MENUJU PERTANIAN RAMAH LINGKUNGAN - I Putu Eka Indrawan; Ni Luh Putu Yesy Anggreni; Pande Komang Suparyana (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
Mengwi is a village/kelurahan located in Mengwi sub-district, Badung Regency, Bali Region. This village is one of 20 villages and sub-districts in Mengwi sub-district. Mengwi Village is a village that grows in the middle of the city in the Badung Regency area, making agricultural land has the potential for environmentally friendly agricultural development because it is close to water sources and there is almost no contamination on the land. The use of organic fertilizers has begun to be applied by farmers, but the use of pesticides is still applying chemical pesticides. The impact of the use of chemical pesticides is not only harmful to plants and the environment, but can lead to more and more new types of pests and diseases that attack plants. Farmers in Mengwi Village do not use organic pesticides due to their lack of understanding of the application of effective and efficient use of organic pesticides. So that the Farmer Groups in Mengwi Village need to be given knowledge and management skills in Agro- Entrepreneurship towards environmentally friendly and sustainable agriculture. The method used in this community service activity is through counseling, training and assistance to farmer groups for 3 months month. The results of community service activities showed that after training and counseling, farmers were able to know the pests that attacked their agricultural land and their control techniques. Farmers can also carry out post-harvest handling which provides higher economic value than before being given training. In general, farmers who participated in the training showed a good response and were active during this activity. At the end of the training and extension, farmers know the costs and marketing efficiency of the Cabbage commodity on their farm.